The Impact of the Internal Public Audit in Local Public Administration – the Evaluation of the Decision-Making System: Array - Ardeleanu (Trifu), Nicoleta (Journal of Danubian Studies and Research, 2020)
In order to strengthen the internal control system, to pursue the efficient spending of public funds and to improve the activities of the public entity, we consider that the purpose of exercising the internal audit must guarantee the fulfillment of the established objectives. The approach, however, differs depending on the organizational culture, the functions of the organization and the functions of management. Based on these realities, the internal audit will evaluate and express the opinion on: the efficiency of actions and decisions taken by the entity’s management regarding compliance with regularity, risk management, organization of internal control systems, ensuring transparency of activities and decisions taken, and how to achieving the set objectives in an efficient and effective manner.